Ongoing behavioral state information signaled in the lateral habenula guides choice flexibility in freely moving rats - Baker, Phillip M.; Oh, Sujean E.; Kidder, Kevan S.; Mizumori, Sheri J. Y. (Frontiers in Behavioral Neuroscience, 2015)
The lateral habenula (LHb) plays a role in a wide variety of behaviors ranging from maternal care, to sleep, to various forms of cognition. One prominent theory with ample supporting evidence is that the LHb serves to relay basal ganglia and limbic signals about negative outcomes to midbrain monoaminergic systems. This makes it likely that the LHb is critically involved in behavioral flexibility as all of these systems have been shown to contribute when flexible behavior is required. Behavioral flexibility is commonly examined across species and is impaired in various neuropsychiatric conditions including autism, depression, addiction, and schizophrenia; conditions in which the LHb is thought to play a role. Therefore, a thorough examination of the role of the LHb in behavioral flexibility serves multiple functions including understanding possible connections with neuropsychiatric illnesses and additional insight into its role in cognition in general. Here, we assess the LHb’s role in behavioral flexibility through comparisons of the roles its afferent and efferent pathways are known to play. Additionally, we provide new evidence supporting the LHb contributions to behavioral flexibility through organization of specific goal directed actions under cognitively demanding conditions. Specifically, in the first experiment, a majority of neurons recorded from the LHb were found to correlate with velocity on a spatial navigation task and did not change significantly when reward outcomes were manipulated. Additionally, measurements of local field potential (LFP) in the theta band revealed significant changes in power relative to velocity and reward location. In a second set of experiments, inactivation of the LHb with the gamma-aminobutyric acid (GABA) agonists baclofen and muscimol led to an impairment in a spatial/response based repeated probabilistic reversal learning task. Control experiments revealed that this impairment was likely due to the demands of repeated switching behaviors as rats were unimpaired on initial discrimination acquisition or retention of probabilistic learning. Taken together, these novel findings compliment other work discussed supporting a role for the LHb in action selection when cognitive or emotional demands are increased. Finally, we discuss future mechanisms by which a superior understanding of the LHb can be obtained through additional examination of behavioral flexibility tasks.